2005
DOI: 10.1128/ec.4.11.1934-1941.2005
|View full text |Cite|
|
Sign up to set email alerts
|

snRNA and Heterochromatin Formation Are Involved in DNA Excision during Macronuclear Development in Stichotrichous Ciliates

Abstract: Several models for specific excision of micronucleus-specific DNA sequences during macronuclear development in ciliates exist. While the template-guided recombination model suggests recombination events resulting in specific DNA excision and reordering of macronucleus-destined sequences (MDS) guided by a template, there is evidence that an RNA interference-related mechanism is involved in DNA elimination in holotrichous ciliates. We describe that in the stichotrichous ciliate Stylonychia, snRNAs homologous to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 30 publications
0
43
1
Order By: Relevance
“…However, some IESs in Stylonychia and Oxytricha are smaller than the observed 26–27 nt small RNAs [29], [32], which are also smaller than a nucleosome core particle. This poses a challenge, because small RNAs would be unable to mark such IESs precisely.…”
Section: Discussionmentioning
confidence: 70%
“…However, some IESs in Stylonychia and Oxytricha are smaller than the observed 26–27 nt small RNAs [29], [32], which are also smaller than a nucleosome core particle. This poses a challenge, because small RNAs would be unable to mark such IESs precisely.…”
Section: Discussionmentioning
confidence: 70%
“…Macronuclear development is slightly delayed during the first DNA amplification stage and is arrested in the polytene chromosome stage of the macronuclear anlage (Figure 1A). Upon TSA treatment, IES (internal eliminated sequence) excision is defective [31] and incubation of cells with the C646 inhibitor at the beginning of sexual reproduction largely prevents the accumulation of H3K9ac/K14ac at the 5′-end of this stage (Additional file 3). Furthermore, we observed that methylated cytosines at both nanochromosomes mdp1 and mdp2 remained present during macronuclear development, whereas after incubation with TSA the DNA remained unmethylated (Figure 4A, B).…”
Section: Resultsmentioning
confidence: 99%
“…2], may discard close to 98% of its MIC DNA during MAC development (36). Yet an earlier paper suggested that its sRNAs are more consistent with the scan RNA model (88); however that inference was based only on hybridization, with no sequence analysis, and numerous other factors could have affected these early results.…”
Section: Bodymentioning
confidence: 99%